Attitudes in didactic change: design and validation of a questionnaire of Primary Education teachers’ attitudes toward the teaching of the Nature of Science and Technology - García-Marigómez, Carmela; Ortega-Quevedo, Vanessa; Gil-Puente, Cristina (Frontiers in Education, 2026)
IntroductionNeglecting the role of attitudes in didactic change is a serious obstacle to progressing toward the inclusion of the Nature of Science and Technology (NoST) in the classroom and achieving a scientific culture that enables the development of a critical and socially engaged citizenship capable of addressing contemporary societal challenges.MethodFor this reason, this study presents the design and validation of an assessment tool that allows attitudes to be collected in a holistic way, taking into account the cognitive, affective and conative components of trainee and practicing Primary School (PS) teachers toward the teaching of NoST. For this purpose, an instrumental-psychometric study was carried out. A sample of 210 subjects participated in the validation of the questionnaire.ResultsThe statistical analyses of the scale show that it has an adequate content validity, an appropriate construct validity with a good fit to the theoretical model, and a high level of reliability. Furthermore, a first approximation to the description of the attitudinal profile indicates that thereis, in general, a positive attitude toward NoST teaching.DiscussionIt is concluded, on the one hand, that the instrument is optimal and adequate for assessing attitudes and, on the other hand, that teacher training should consider both the cognitive and affective factors that hinder the transformation of educational practices in the field of science teaching.